Tissue engineering strategies for organ regeneration - Sultana, Naznin; Bandyopadhyay-Ghosh, Sanchita, 1971-; Soon, Chin Fhong, 1974- (Boca Raton : CRC Press, Taylor & Francis Group, 2020)
Tissue Engineering Strategies for Organ Regeneration addresses the existing and future trends of tissue engineering approaches for organ/tissue regeneration or repair.This book provides a comprehensive summary of the recent improvement of biomaterials used in scaffold-based tissue engineering, and the tools and different protocols needed to design tissues and organs. The chapters in this book provide the in-depth principles for many of the supporting and enabling technologies including the applications of BioMEMS devices in tissue engineering, and the combination of organoid formation and three dimensional (3D) bioprinting. The book also highlights the advances and strategies for regeneration of three-dimensional microtissues in microcapsules, tissue reconstruction techniques, andinjectable composite scaffolds for bone tissue repair and augmentation. Key Features: Addresses the current obstacles to tissue engineering applications Provides the latest improvements in the field of integrated biomaterials and fabrication techniques for scaffold-based tissue engineering Shows the influence of microenvironment towards cell-biomaterials interactions Highlights significant and recent improvements of tissue engineering applications for the artificial organ and tissue generation Describes the applications of microelectronic devices in tissue engineering Describes different current bioprinting technologies
"A Science Publishers Book" -- title page.
OCLC-licensed vendor bibliographic record.
Keywords: Tissue scaffolds; Guided tissue regeneration; Tissue engineering; Biomedical materials; Regeneration (Biology); MEDICAL / Biotechnology; TECHNOLOGY / Material Science